SAT0131 SAFETY AND EFFECTIVENESS OF DISEASE-MODIFYING ANTI-RHEUMATIC DRUGS (BDMARDS) IN OLDER ADULTS WITH RHEUMATOID ARTHRITIS: A RETROSPECTIVE COHORT STUDY. (June 2019) - Akter, Ripa; Maksymowych, Walter P.; Martin, Liam; Hogan, David
Abstract : Background: Rheumatoid arthritis is common among older adults and biological disease-modifying antirheumatic drugs (bDMARDs) are effective in treating this population. However, older patients reportedly experience more adverse events (AEs) with effectiveness being either equivalent or worse than younger patients. Objectives: Our primary objective was to compare the AEs associated with the use of bDMARDs and their relative effectiveness in three age groups: Group 1 (75+), Group 2 (65-74 years) and Group 3 (55-64 years) patients. We explored if sex, disease activity, baseline functional impairment, and the type of bDMARDs used differed across the three age groups as a secondary objective. Methods: A retrospective cohort study of adults 55+ with RA seen between Jan 1, 2007 and July 31, 2009 was performed utilizing the RAPPORT (Rheumatoid Arthritis Pharmacovigilance Program and Outcomes Research in Therapeutics) database housed in Edmonton, Alberta, Canada. Baseline characteristics (age, sex, DAS28 score, HAQ score, types of bDMARDs used), drug effectiveness (based on DAS28 score) and associated AEs were compared across the three age groups. Descriptive statistics (Mean, SD, percentages) were used. An intention to treat analysis with chi-square testing for categorical variables and t testing for continuous ones were used to test for the significance of differences found. Results: A total of 333 patients met our entry criteria (69.4% female, 30.6% male) with 52, 125 and 156 from groups 1, 2 and 3 respectively. Group 1 patients had a significantly higher mean HAQ score (2.16) compared to the younger groups (P<0.0.5), and a mean DAS28 (6.52) score significantly higher than the 55-64 group (P<0.05). Group 1 patients were also more likely to experience AEs (p<0.05), which were more likely to be infectious (p<0.05), life threatening/severe (p<0.05), cause discontinuation of treatment (p<0.05) and multiple (p<0.05) compared to the two younger groups. We also interestingly found the remission rate to be significantly higher in Group 1 patients compared to Group 2 (p<0.05). Etanercept was the most commonly used drug among all age groups. Rituximab and abatacept were much less frequently used. Rate of AEs and therapy effectiveness did not differ significantly by sex across the three age groups. Conclusion: Older adults aged 75+ treated with bDMARDs for RA are at a significantly higher risk of AEs, which should be included in the treatment discussion. The higher remission rate in those 75+ compared to those 65-74, which has not been reported previously, warrants further study. References: [1] Dalal D, Duran J, Brar T, Alqadi R, Halladay C, Lakhani A, Rudolph J. Efficacy and safety of biological agents in the older rheumatoid arthritis patients compared to Young: A systematic review and meta-analysis. Seminars in Arthritis and Rheumatism. 2018 Jul 31. pii: S0049-0172(18)30162-8 [Epub ahead of print]. [2] . Sugihara T, Harigai M. Targeting Low Disease Activity in Elderly-Onset Rheumatoid Arthritis: Current and Future Roles of Biological Disease-Modifying Antirheumatic Drugs. Drugs & Aging. 2016; 33(2): 97-107. [3] . Filippini M, Bazzani C, Favalli E, et al. Efficacy and Safety of Anti-Tumour Necrosis Factor in Elderly Patients with Rheumatoid Arthritis: An Observational Study. Clinical Reviews in Allergy & Immunology. 2009; 38(2-3): 90-96. Disclosure of Interests: Ripa Akter: None declared, Walter P Maksymowych Grant/research support from: AbbVie, Pfizer, Janssen, Novartis, Consultant for: AbbVie, Eli Lilly, Boehringer, Galapagos, Janssen, Novartis, Pfizer and UCB Pharma; Chief Medical Officer for Canadian Research and Education Arthritis, Liam Martin: None declared, David Hogan: None declared